2002
DOI: 10.1023/a:1020181124118
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of war experiences and exile‐related stressors to levels of psychological distress among Bosnian refugees

Abstract: This study examined the relative contribution of 2 exile-related variables--social isolation and daily activity level--and war experiences of violence and loss, to levels of PTSD and depressive symptomatology in 2 groups of Bosnian refugees, 1 clinical group (N = 59) and the other a nonclinical community (N = 40) group. As hypothesized, exposure to war-related violence was highly predictive of PTSD symptoms in both groups; in addition, social isolation was significantly related to PTSD symptomatology in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
119
1
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(145 citation statements)
references
References 39 publications
8
119
1
8
Order By: Relevance
“…doi: 10.1007/s11469-006-9036-6 relationships are quite robust. We also found, consistent with some past research (e.g., Hunt & Gakenyi, 2005;Miller et al, 2002a;Spasojevic et al, 2002), that the experience of exile may make refugees more prone to experiencing mental health problems than similarly traumatized war survivors who remain in their home counties. Specifically, we found that, even when controlling for past exposure to wartime trauma and a host of demographic variables, the Bosnian refugees in our sample suffered from significantly greater levels of PTSD (though not anxiety or depression) than their Bosnian resident cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…doi: 10.1007/s11469-006-9036-6 relationships are quite robust. We also found, consistent with some past research (e.g., Hunt & Gakenyi, 2005;Miller et al, 2002a;Spasojevic et al, 2002), that the experience of exile may make refugees more prone to experiencing mental health problems than similarly traumatized war survivors who remain in their home counties. Specifically, we found that, even when controlling for past exposure to wartime trauma and a host of demographic variables, the Bosnian refugees in our sample suffered from significantly greater levels of PTSD (though not anxiety or depression) than their Bosnian resident cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Second, we explored whether systematic differences in psychological distress existed between Bosnian residents and refugees. We anticipated that, consistent with the results of several researchers (e.g., Miller et al, 2002a;Miller et al, 2002b;Hunt & Gakenyi, 2005), Bosnian refugees, perhaps due to the difficulties associated with beginning a new life in a foreign country, would report greater levels of anxiety, depression, and PTSD than Bosnian residents.…”
supporting
confidence: 63%
“…It must however be taken into account that one third of the women of the refugee sample did not report events due to the high distress caused by remembering. In addition to this underreporting in the refugee sample, it seems rather to be the witnessing of violence that is etiologically linked to the development of PTSD symptoms, whereas loss is more likely to be associated with the development of depressive symptomatology (Miller et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…Mental health impairment in these samples seems to be more severe than in non-refugee as well as internally displaced civilians (Porter & Haslam, 2001). Persisting clinical levels of trauma were found in studies conducted several years after resettlement in a refugee camp or host country (Miller et al, 2002;Momartin & al, 2003). Most prominent is the finding that 2 decades after the resettlement of Cambodian refugees in the United States, 62% were diagnosed as suffering of PTSD (Marshall et al, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…All this has a solid impact on their health and their wellbeing, and has led to long-term emotional scars and mental health problems with children and adolescents [2,5,11]. Exposure to war violence and social isolation are highly predictive symptoms of PTSD; depressive symptomatology was accounted for, primarily by the exilerelated stressors [12]. Failure to resolve moderate to severe traumatic reactions may result in long-lasting consequences on adolescent ability to engage in productive behavior and function socially, academically, professionally, and personally adequate [5,13].…”
Section: Introductionmentioning
confidence: 99%